A New Derivative of Core–Shell Magnetic Chitosan Biopolymer: Synthesis, Characterization and Application for Adsorption of Lead and Copper Ions. Issue 6 (2nd March 2016) - Hossein Beyki, Mostafa; Miri, Simin; Shemirani, Farzaneh; Bayat, Mehrnoosh; Rashidi Ranjbar, Parviz
Abstract : In this research, a new derivative of core–shell magnetic chitosan biopolymer was prepared. The core magnetic Fe3 O4 nanoparticles were synthesized by a simple and fast sonochemistry route within 10 min. Fe 3+ ions and sodium thiosulfate were used as the iron source and reducing agent, respectively. Then shell chitosan grafted with 5‐acrylamido‐1, 10‐phenanthroline was cross‐linked to the magnetic core with glutaraldehyde. The new material was characterized with transmission and scanning electron microscopy, infared spectroscopy, X‐ray diffraction, thermogravimetry and vibrating sample magnetometer technique. The characterization analysis revealed that grafted chitosan had been assembled on the surface of magnetic nanoparticles at a high density and showed enough magnetic response for magnetic separation. The prepared composite was used for the removal of Pb and Cu ions from environmental samples. The adsorption capacity within 10 min interaction time was 111.0 and 33.3 mg g −1 for Pb(II) and Cu(II), respectively. Abstract : Magnetic Fe3 O4 is prepared by a simple and fast sonochemistry route and is applied for fabrication of a new derivative of magnetic chitosan biopolymer. Phenanthroline anchored magnetic chitosan is a good candidate for adsorption and removal of lead and copper from environmental samples. It has a good adsorption capacity and can easily be separated by a magnetic field.